Tandem "click" reactions at acetylene-terminated Si(100) monolayers - Ciampi, Simone; James, M.; Michaels, P.; Gooding, J. (American Chemical Society, 2011)
We demonstrate a simple method for coupling alkynes to alkynes. The method involves tandem azide-alkyne cycloaddition reactions ("click" chemistry) for the immobilization of 1-alkyne species onto an alkyne modified surface in a one-pot procedure. In the case presented, these reactions take place on a nonoxidized Si(100) surface although the approach is general for linking alkynes to alkynes. The applicability of the method in the preparation of electrically well-behaved functionalized surfaces is demonstrated by coupling an alkyne-tagged ferrocene species onto alkyne-terminated Si(100) surfaces. The utility of the approach in biotechnology is shown by constructing a DNA sensing interface by derivatization of the acetylenyl surface with commercially available alkyne-tagged oligonucleotides. Cyclic voltametry, electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy, and X-ray reflectometry are used to characterize the coupling reactions and performance of the final modified surfaces. These data show that this synthetic protocol gives chemically well-defined, electronically well-behaved, and robust (bio)functionalized monolayers on silicon semiconducting surfaces. © 2011 American Chemical Society.